Puppets for Blessings: Enhancing the Skills of Educators and Children's Ministry Workers Through Puppet - Tiladuru, Vena Melinda; Nenny Natalina Simamora; Desmiyati Rambu Loda; Alvionita Rambu Ngguna (Edumedia Solution, 2026)
This community service program titled